The Increasing Surface Ozone and Tropospheric Ozone in Antarctica and Their Possible Drivers - Pankaj Kumar (63234); Jayanarayanan Kuttippurath (10979795); Peter von der Gathen (10979798); Irina Petropavlovskikh (10979801); Bryan Johnson (4634659); Audra McClure-Begley (10979804); Paolo Cristofanelli (8294247); Paolo Bonasoni (773092); Maria Elena Barlasina (10979807); Ricardo Sánchez (10979810) (2021)
A comprehensive analysis of the temporal evolution of tropospheric ozone in Antarctica using more than 25 years of surface ozone and ozonesonde measurements reveals significant changes in tropospheric ozone there. It shows a positive trend in ozone at the surface and lower and mid-troposphere, but a negative trend in the upper troposphere. We also find significant links between different climate modes and tropospheric ozone in Antarctica and observe that changes in residual overturning circulation, the strength of the polar vortex, and stratosphere–troposphere exchange make noticeable variability in tropospheric ozone. Therefore, this study alerts of increasing ozone concentration in Antarctica, which would have a profound impact on the future climate of the region as tropospheric ozone has warming feedback to the Earth’s climate.